Prepare and protect : safer behaviors in laboratories and clinical containment settings - Kaufman, Sean G. (Washington, DC : ASM Press, 2020)
'Florence Nightingale said,'The first requirement of a hospital is that it should do the sick no harm.' This statement served as the backbone of infection control for health care settings. I don't believe any scientist (of the right mind) has ever come to work with the goal of killing themselves or those with whom they work. Historically, there are several examples of scientists doing things to protect themselves when working in biological laboratories. However, it is my opinion the profession of biosafety formally started within the United States in 1941 when Secretary of War Henry Stimson stated,'Because of the dangers that might confront this country from potential enemies employing what may be broadly described as biological warfare, it seems advisable that investigations be initiated to survey the present situation and the future possibilities.' In 1942, George Merck established the War Reserve Services under the stated premise,'There is but one logical course to pursue, namely, to study the possibilities of such warfare from every angle, make every preparation for reducing its effectiveness, and thereby reduce the likelihood of its use.''--
Includes index.
Keywords: Laboratory infections -- prevention & control (PC).